58.4k views
1 vote
5x + 4x - x

9x
Explain mistake:

Correct answer:


2(x + 5)
2x + 5
Explain mistake:

Correct answer:


5 - (x - 2)
5 - x - 2
3 - x
Explain mistake:

Correct answer:


-3(2x - 5)
-6x - 15
Explain mistake:

Correct answer:


2x + 3 + 4x
9x
Explain mistake:

Correct answer:



x + 3x + 6x

10x {}^(2)
Explain mistake:

Correct answer:​

1 Answer

0 votes
Answer:
Correct answer:
1). 8x
2). 2x + 10
3). 7 - x
4). 6x + 3
5). 10x

Step-by-step explanation:

1). 5x + 4x - x
= 9x - x
= 8x

Mistake: 9x - x is 8x not 9x

2). 2(x + 5)
= 2x + 10

Mistake: When multiply 2(x + 5) you have to take 2(x) + 2(5) = 2x + 10 not 2(x) + 5 = 2x + 5

3). 5 - (x - 2)
= 5 - x + 2
= 7 - x

Mistake: when a minus sign is in front of a parenthesis the sign in between the two terms in the parentheses needs to change. 5 - (x - 2) = 5 - x + 2 not 5 - x - 2.

4). 2x + 3 + 4x
= 6x + 3

Mistake: Combine like terms. Add the number with variable to the number with variable. And the number without variable to the number without variable.

5). x + 3x + 6x
= 10x

Mistake: When add the number with the same variable. Only the coefficient increase not the exponent itself. But when multiply, both the coefficient and exponent increase.







User Codingwithmanny
by
5.1k points